Interelasi latar belakang pendidikan orang tua dengan perilaku disiplin belajar pendidikan kewarganegaraan di SMA Negeri 21 Bandung - Edi Kusnadi; Nani Nur'aeni; Ahmad Khoerul Umam (Universitas Ahmad Dahlan, 2018)
Basically, education which is one of the most important factor for human being aims to achieve maturity and perfection in individual behaviour, especially for parents they have central role to bring their chidren up in familly environment. This research aims to figure out the conection between parents’ educational background and students’ dicipline behavior in studying citizenship education, conducted in SMAN 21 Bandung using quantitaive aproach within likert scale model and ordinal data. The result of the the research shows that there is a relationship between parents’ educational background and students’ attitudes toward learning process in the school. This relationship is verified from the result of categorical analysis of the correlation between both variable. The result shows that parents’ ecuational background is at midle category about 74,5 % and learning behaviour students’ is at high category about 60% from 90 students; in spite of not sufficient, it is still a good result. It verifies the connection between parents’ educational background which is at middle category of 74,4% and students’ learning behaviour which is at strong or high category from 60% for 90 students